The BMI impact on thyroidectomy-related morbidity; a case-matched single institutional analysis - Sascha Vaghiri; Jasmin Mirheli; Dimitrios Prassas; Stephen Fung; Sami Alexander Safi; Georg Fluegen; Wolfram Trudo Knoefel; Levent Dizdar (BMC Surgery)
Abstract Background Obesity is associated with an increased risk of postoperative morbidity. We aimed to analyze the impact of BMI on surgical complications in patients undergoing thyroidectomy. Methods This retrospective study was conducted in a single academic center. A total of 484 patients with open total thyroidectomy were considered eligible. These patients were divided in the non-obese (BMI < 30 kg/m2) and obese (BMI ≥ 30 kg/m2) groups. A 1:2 case matching based on demographic (age and gender) and clinical (benign/malignant disease) variables was performed to generate homogenous study groups. A comparative analysis was carried out to show the differences between the two groups in terms of the occurrence of surgery-related outcomes. Results After case matching, 193 non-obese and 98 obese patients were included in the final analysis. There was no statistically significant difference in the rate of primary outcomes in the non-obese and obese groups: hypoparathyroidism (transient: 29% versus 21.4%, p = 0.166; permanent: 11.4% versus 15.3%, p = 0.344, respectively) and recurrent laryngeal nerve palsy (transient: 13.9% versus 11.2%, p = 0.498; permanent: 3.1% versus 2.0%, p = 0.594, respectively). A BMI ≥ 30 kg/m2 was associated with a significantly longer operative time (p = 0.018), while other secondary outcomes were not significantly affected by BMI. Conclusions Despite prolonged operative times in obese patients, total thyroidectomy could be performed safely and without increased risk of surgery-related morbidity, regardless of BMI. Clinical trial number Not applicable.